Tada, kada, šiada, andai, idant - Valeckienė, Adelė (Baltistica, 1979)
Lith. tada, kada, šiada, andai, idant The author discusses the origin of the Lithuanian forms tada, kada, šiada; kadai, kadaise kadan, kadangi; andai; idant etc. and concludes the following: The Lithuanian compounds of this type are related to the corresponding Slavic and Indo-Iranian compounds. The element -d- in the Lithuanian compounds belongs to the stems of the demonstrative pronoun *do/*de (OP din, dīgi) as the same element in OInd. tadā́, kadā́, yadā́. The element -g- in the Slavic and Baltic compounds (OCS togda, Russ. тогда, OPol. tegdy, Czech, tehda etc., Lith. tagačiaus, tagatės, Latv. tagad) could be reconstructed from the particle *go (i. e. the one related to Slavic же, OInd. ghā̆, ha, Gk. γε, γα, Goth, -k in mi-k “me”).